IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR RUMAH DETENSI IMIGRASI (RUDENIM) DI KOTA PEKANBARU - Putra, Dedi Gunawan; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Immigration detention is a temporary shelter foreigners who violate the legislation imposed immigration measures and pending repatriation to their countryThis study aims to determine how the implementation and the factors that influence in the Standard Operating Procedures Rudenim in Pekanbaru, to conform with regulations that the Director General of Immigration NO IMI. 1917-OT.02.01 YEAR 2013 on Standard Operating Procedures Rudenim.This study uses qualitative methods with data collection by interview, observation and literature study. Interviews were conducted with research informants defined by snowball sampling technique.The results showed that the implementation of Standard Operating Procedures Immigration Detention House (Rudenim) in the city of Pekanbaru is still not running smoothly or less effective. Due to the vagueness and contradictions in the statement of basic measures and policy objectives which resulted in the disciplinary rules pertaining to the Standard Operating Procedure regarding temporary exit permits for Deteni without escort. concluded that the dominant factor influencing factor is the policy. Where the lack of policy of the Central Government and the response or lack good relationship between immigration detention by the central government such as the Ministry of Justice and Human Rights and the Minister of Foreign Affairs so as to make make the implementation of Standard Operating Procedures immigration detention is not running smoothly.Keywords: Implementation, Standard Operating Procedures, Rudenim